Health literacy in patients with pulmonary embolism: development and validation of the HeLP (Health Literacy in Pulmonary Embolism)-Questionnaire - Fischer, Simone; Kalch, Anja; Küchler, Constanze; Albani, Aliscia Rebecca; Bilandzic, Helena; Horenkamp-Sonntag, Dirk; Berghaus, Thomas M.; Meisinger, Christine; Kirchberger, Inge (Frontiers in Public Health, 2023)
Background Pulmonary embolism (PE) is a common cardiovascular disease and health literacy is necessary to deal with its consequences after the acute event. The aim of this study was to develop and validate a new questionnaire to measure PE-specific health literacy. Methods A mixed-methods design with qualitative and quantitative elements was used in the development process. A literature review about health literacy concepts and instruments and interviews with patients with PE and clinicians were conducted. Quantitative analyses included factor analyses, item response theory with a graded partial credit model, and reliability analyses in different test and validation samples. Furthermore, convergent and known-groups validity and responsiveness were assessed. Results The qualitative results supported a concept of PE-related health literacy with four main topics: dealing with PE-related health information, disease management, health-related selfcare, and social support. An initial item pool of 91 items was developed. Further interviews and an online survey with patients with PE (n = 1,013) were used to reduce the number of items and to confirm structural validity. Confirmatory factor analyses in the final evaluation study with patients with PE (n = 238) indicated a good model fit of the four-factor structure. The Health Literacy in Pulmonary Embolism (HeLP)-Questionnaire showed good reliability (Cronbach’s alpha: 0.82 to 0.90). All four subscales were responsive toward receiving a brochure with PE-related health information. Conclusion The newly developed German HeLP Questionnaire comprises 23 items in four domains and showed good psychometric properties. Further evaluation of the questionnaire in different samples of patients with PE is needed.